The work of return to work. Challenges of returning to work when you have chronic pain: a meta-ethnography - Martin Underwood; Mary Grant; Kate Seers; Robert Froud; Joanne O-Beirne-Elliman (BMJ Open)
Aims To understand obstacles to returning to work, as perceived by people with chronic non-malignant pain and as perceived by employers, and to develop a conceptual model.Design Synthesis of qualitative research using meta-ethnography.Data sources Eleven bibliographic databases from inception to April 2017 supplemented by citation tracking.Review methods We used the methods of meta-ethnography. We identified concepts and conceptual categories, and developed a conceptual model and line of argument.Results We included 41 studies. We identified three core categories in the conceptual model: managing pain, managing work relationships and making workplace adjustments. All were influenced by societal expectations in relation to work, self (self-belief, self-efficacy, legitimacy, autonomy and the meaning of work for the individual), health/illness/pain representations, prereturn to work support and rehabilitation, and system factors (healthcare, workplace and social security). A mismatch of expectations between the individual with pain and the workplace contributed to a feeling of being judged and difficulties asking for help. The ability to navigate obstacles and negotiate change underpinned mastering return to work despite the pain. Where this ability was not apparent, there could be a downward spiral resulting in not working.Conclusions For people with chronic pain, and for their employers, navigating obstacles to return to work entails balancing the needs of (1) the person with chronic pain, (2) work colleagues and (3) the employing organisation. Managing pain, managing work relationships and making workplace adjustments appear to be central, but not straightforward, and require substantial effort to culminate in a successful return to work.